Predictors for Actual COVID-19 Vaccine Uptake and Intended Booster Dosage among Medical Students of an Osteopathic Medical School in New York - Taysir Al Janabi; Maria Pino (MDPI AG, 2021)
Exploring future physicians' attitudes toward vaccination is crucial as physicians' recommendation is the top predictor for individuals to receive vaccines. This study explored the uptake of COVID-19 vaccines and the intention for future booster dose uptake among students at the New York Institute of Technology College of Osteopathic Medicine (NYITCOM). Predictors for actual vaccine and intended booster uptake were also examined. An electronic survey was distributed to Osteopathic Medical Students (OMS I-IV) in the Spring of 2021. A total of 1331 students received the survey, with 316 responses received (24%). In total, 95.3% (301/316) of the respondents reported that they already received vaccines, while 3.1% (13/316) reported that they had not yet received a vaccine. Moreover, 88.9% of the respondents (281/316) were in favor of a booster dose, which was a strong predictor for actual vaccine uptake. We identified that the Asian race, pharmaceutical mistrust, building immunity via vaccines, adequate vaccine testing, and willingness to get non-U.S. manufactured vaccines are the most significant predictors for willingness to accept a booster dose. A very high COVID-19 vaccine uptake among NYITCOM OMS was found in our study. The study also observed a high acceptance of an additional dose of the COVID-19 vaccine in the future.